Personality Dimensions of Counselors\' Competency from the Perspective of Successful Counselors: A Qualitative Study - Morteza Karami; Mousa Choupani (Journal of Qualitative Research in Health Sciences, 2019)
Introduction: Transformation of society from a simple and elementary state to a complicated and complex one, makes necessary the day-to-day need of the specialists of mental health realm, especially counselors. The aim of this study was to investigate the personality dimensions of counselors' Competency from the perspective of successful counselors. Method: This qualitative study was conducted using phenomenological approach. Among counselors of Shamim counseling centers of Sepah in 2016, 20 counselors were selected using purposive sampling, and then, interviewed. All the interviews were tape-recorded and transcribed line by line, and finally, were analyzed through content analysis. Results: After data analysis, 14 main themes (responsibility, divergent thinking, disciplined, realism, flexibility, courage, openness to criticism, adventure, hard worker, creativity, cautiousness, Authenticity, hopefulness, and high adjustment) and 46 sub-themes in the field of personality dimensions of counselors' competencies were identified and classified. Conclusion: The results of this study can help counselors to evaluate their competency and self-efficacy, and can be useful in developing counseling training programs and appointing competent counselors by decision-makers and policymakers in the field of mental health.